2006
DOI: 10.1002/jcb.21108
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis as a possible mechanism of infertility in Echinococcus granulosus hydatid cysts

Abstract: Echinococcus granulosus is a parasitic cestode causing hydatidosis in intermediate hosts (human and herbivorous). Most symptoms of the disease occur by the pressure exerted on viscera by cysts that are formed upon ingestion of the parasite eggs excreted by definitive hosts (canines). Protoscoleces, the developmental form of the parasite infective to definitive hosts, are formed in the germinal nucleated layer of fertile hydatid cysts. For unknown reasons, some cysts are unable to produce protoscoleces (inferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 39 publications
(52 reference statements)
2
51
0
Order By: Relevance
“…Kang et al (2008Kang et al ( , 2009) found a significant increase in Caspase 3 in E. granulosus protoscolices exposed to hydrogen peroxide (H 2 O 2 ) and adenosine triphosphate (ATP) compared to control values. The first published study on apoptotic changes in hydatidosis reported a higher level of Caspase 3 in infertile cysts than fertile ones (PAREDES et al, 2007). Accordingly, we propose that decreased apoptosis may enhance cyst survival.…”
Section: Discussionmentioning
confidence: 62%
“…Kang et al (2008Kang et al ( , 2009) found a significant increase in Caspase 3 in E. granulosus protoscolices exposed to hydrogen peroxide (H 2 O 2 ) and adenosine triphosphate (ATP) compared to control values. The first published study on apoptotic changes in hydatidosis reported a higher level of Caspase 3 in infertile cysts than fertile ones (PAREDES et al, 2007). Accordingly, we propose that decreased apoptosis may enhance cyst survival.…”
Section: Discussionmentioning
confidence: 62%
“…[60] Also high level of apoptosis has been reported in E.granulosus hydatid cyst. [42,61,62] Regarding C. rotundus and within this hypothesis, recent studies concluded that the aerial parts extract of this plant exhibit a potential use as antioxidant and apoptosis inducer and explained that the anti-proliferative effect of these extracts is due to induction of apoptosis and suggested the regulation of apoptotic genes may be controlled by their phenolic content, orientin is one of the main flavonoids identified in alcoholic extract. [33] Moreover, the result of Hu et al, [63] confirmed the presence of apoptosis and the existence of CED-3 like apoptotic gene in protoscoleces of E. granulosus and proved that H2O2and hexamenthasone can induce cell apoptosis of protoscoleces in drug-induced apoptosis mechanisms.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 95%
“…Furthermore, some studies evaluated the effect of E. granulosus hydatid fluid on the lymphocytes in 3-day cultures of the T cell line and suggested that the cytotoxicity of hydatid fluid could have resulted from cell cycle arrest (Macintyre et al 2000). Programmed cell death may be a cellular mechanism underlying hydatid cyst infertility (Paredes et al 2006). On the other hand, molecules involved in DNA repair in the germinal layer of fertile hydatid cysts and in protoscoleces, such as EgRAD9, may allow preserving the fertility of hydatid cysts present (Cabrera et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…As a result, it is of highest importance to decode and understand the process and the role of apoptosis induced or monitored by parasites in humans (Conchedda et al 2004). In spite of this, several studies provide definitive awareness of parasite-induced host cell apoptosis (Paredes et al 2006;Cabrera et al 2008). Apoptosis is a type of programmed cell death that can be characterized biochemically and morphologically.…”
Section: Introductionmentioning
confidence: 99%